Innovating Lean Six Sigma : A Strategic Guide to Deploying the World's Most Effective Business Improvement Process - Watson-Hemphill, Kimberly; Nissen Bradley, Kristine (McGraw-Hill's AccessEngineering., 2016)
Develop deeper insights into your customer experience. Tackle bigger problems and find better solutions. When it comes to running a business, there is no better way to improve efficiency, increase productivity, and escalate profits than Lean Six Sigma. And there is no better book on how to make it work than Innovating Lean Six Sigma.